Avaliação de parâmetros de repolarização ventricular em pacientes ambulatoriais com psoríase - Schmitz, Giulia Bevilacqua (2020)
Introduction: Psoriasis is a chronic, immune mediated and genetically disease. Cardiovascular diseases seem to occur more frequently in these patients, including a higher risk of arrhythmias. Parameters of ventricular repolarization are considered sensitive to determine the risk of arrhythmias. However, the role of these parameters in patients with psoriasis is not well defined. Objectives: We sought to evaluate and compare parameters of ventricular repolarization between outpatients with psoriasis and healthy control patients. Methodology: Case-control study. The target population consisted of patients with outpatient follow-up psoriasis from a dermatology service of a tertiary hospital in south of Brazil. The controls were healthy subjects selected from a private cardiology outpatient clinic, located in the same region covered by the cases. Results: A total of 130 individuals were evaluated, with a mean age of 53.1±15.1 years. The mean age of individuals with psoriasis was lower than controls (49,2 ± 14,2 vs. 57 ± 15,1; P=0,003). The QTCmín was superior in patients with psoriasis (379,2 ±26,4 ms versus 358,3 ± 27 ms; P<0,001). On the other hand, the median dispersion of the absolute QT interval (QTd; 14.6 ms, 10.7 - 21.2 ms in the psoriasis versus 36.8 ms group, 30.2 - 42.7 ms in the control group; P<0.001) and corrected (QTdc; 15.7 ms, 11.5 - 24.2ms in the psoriasis versus 39.8 ms group, 32.8 - 46.6 ms in the control group; P<0.001) were lower in patients with psoriasis. The mean peak intervals at the end of the absolute T wave (Tp-e; 91.7 ± 11.6 ms versus 96.0 ± 9.2 ms in the control group; P=0.024) and corrected for the QTc interval (Tp-e/QTc; 0.22 ± 0.03 versus 0.23 ± 0.03 in the control group; P=0.024) were also lower in patients with psoriasis. QTCmáx and Tp-e/QT showed no significant difference between the groups. There was no correlation between PASI and CRP with the repolarization measurements. Conclusion: In outpatients with psoriasis in southern Brazil, the QTd, Tp-e and Tp- e/QT values were lower than those observed in healthy controls.